A study of construction safety management in GanZhou, China - Zhang, Zhen (2023)

(untitled)
Safety is a fundamental requirement for the stability and development of human society, and safety production is the basic guarantee for the life and health of employees. In recent years, although the safety management level of China's construction industry has been continuously improving, major safety accidents in engineering construction projects still occur from time to time, resulting in huge economic losses and casualties, and extremelynegative social impact. Therefore, this study aimed to study and analyzeon the current situation of construction safety supervision and management in China and Jiangxi Qichen construction company through literature review, questionnaire survey and interview methods Adetailed analysis was conducted on the problems existing in China's construction safety supervision system from the perspectives of government supervision and management, industry supervision and management, enterprise supervision and management, and social supervision and management. The experience of construction safety supervision and management in developed countries abroad was summarized and used for references. Then, a more in-depth study has been conductedon the operational mechanism, current situation and problemsof the construction safety supervision and management systemin Jiangxi Qichen construction company, causes of construction safety accidents in the company, followed by, proposing optimization measures and suggestions to improve the safety management system of the company. This article analyzes the shortcomings of the current construction safety supervision and management system of construction companies. At the same time, this article found thatJiangxi Qichen Construction Company is lack of effective implementation measures and tracking mechanisms, which may lead to false appearances in supervision and management. The role of industry organizations in supervision and management has not been fully utilized, and Jiangxi Qichen Construction Company's enthusiasm for participating in safety supervision and management for its own interests is not high.As a conclusion, the legal and regulatory mechanisms, organizational mechanisms, cultural mechanisms,and information management mechanisms for building safety are jointly needed tobuild a guarantee platform for the smooth operation of the building safety supervision and management systemin a company.